A Frequency Domain Design Method for PID Controllers - Barnes, T. J. D.; Wang, L.; Cluett, W.R. (American Control Conference, 1993, 1993)
This paper will provide a frequency domain design method for PID controllers, which is based on a least-squares fit of the actual to the desired open-loop Nyquist plot. The algorithm is simple and achieves a unique minimum of the sum of the squared errors for a given desired response. Graphical measures will be introduced which will aid the designer in assessing whether the desired performance is achievable with a PID controller.